Pengaruh Pemberian Campuran Pakan dan Perbedaan Rasio Seks pada Pertumbuhan dan Tingkat Reproduksi Jangkrik Ciriling (Grillus mitratus Burm.) - Ida Kinasih; Astuti Kusumorini; Tri Cahyanto; Nurmina Arofah (Al-Kauniyah: Jurnal Biologi, 2013)
Cricket is commonly use as feedstuf for fishes and birds. However, most of market demand for this insect fulfilled by natural harvest. Since they could be an alternative nonconventional protein source for livestock industry, it is needed to develop methods for high cricket biomass production such as find their suitable food plants. During this research, Ciriling cricket (Grillus mitratus Burm.) was fed with various plants and mated with different sex ratio. Pakchoi (Brassica sinensis L.), papaya (Carica papaya L.), and carrot (Daucus carota L.) was combined with common commercial fed of cricket. Changes in food consumption, nymph mortality, body size, egg production, and egg hatching rates were measured in order to find best fed combination and sex ratio. The result showed that combination of standard fed with pakchoi preferred by cricket and produced best growth, highest egg production and egg hatching rates while ratio sex of  1:3 (male:female) produced highest number of eggs and best egg hatching rates.